Lipoprotein diffusion in dense yolk plasma is governed by softness, hydrodynamics, and caging: Insights from MHz-XPCS - Nimmi Das Anthuparambil; Michelle Dargasz; Sonja Timmermann; Anita Girelli; Sebastian Retzbach; Johannes Möller; Wonhyuk Jo; Agha Mohammad Raza; Aliaksandr Leonau; James Wrigley; Frederik Unger; Maddalena Bin; et al. (Proceedings of the National Academy of Sciences, 2026)
Low-density lipoproteins (LDLs) are central to nutrient transport in egg yolk and have emerged as natural nanocarriers for drug delivery. Their biological function critically depends on mobility within densely crowded environments, yet the mechanisms governing their motion remain elusive, largely because conventional techniques cannot access the relevant microsecond timescales. Here, we employ megahertz X-ray photon correlation spectroscopy at the European X-ray Free Electron Laser facility to resolve LDL dynamics in native yolk-plasma. This approach reveals transient caging and memory effects and shows that the combined influence of particle softness and hydrodynamic coupling slows diffusion by nearly two orders of magnitude compared to dilute solutions. However, this reduction could not be scaled with an increase in macroscopic viscosity obtained from rheometry, indicating deviations from the Stokes–Einstein relation. Despite this slowdown, yolk-plasma remains a “sluggish yet liquid state”, balancing dense packing and the fluidity required for lipid release during embryonic development. These results establish a quantitative framework connecting microstructure, hydrodynamics, and transport in crowded soft-matter systems, with implications for developmental biology and nanomedicine.